Prenatal diagnosis and outcomes in 320 fetuses with nasal bone anomalies - Li, Hui; Yao, Yanyi; Zhang, Chengcheng; Qin, Yayun; Zeng, Ling; Song, Jieping; Lu, Li; Wang, Wei; Liu, Lijun (Frontiers in Genetics, 2023)
Object: To investigate the chromosome abnormalities associated with absent or hypoplastic fetal nasal bone. Methods: Patients with fetal nasal bone anomalies(NBA) referred to our center for prenatal diagnosis between 2017 and 2021 were retrospectively evaluated. All these patients underwent chromosomal microarray and/or karyotyping and received genetic counseling before and after testing. Results: Among 320 fetuses with NBA, chromosomal abnormalities were diagnosed in 89 (27.8%) cases, including 53 cases of trisomy 21, which was the most common type of chromosomal aneuploidy, accounting for 59.6% of all detected abnormalities. In addition to aneuploidies, 29 cases of copy number variants (CNVs) were detected. In cases of isolated NBA with low-risk screening results and without other risk factors, the incidence of fetal chromosomal aneuploidies and pathogenic CNVs is 5.3% (7 in 132 cases). Conclusion: This study suggests that parents of fetuses should be informed about the possibility of fetal aneuploidy and pathogenic CNVs and that discussion with the parents is also recommended, providing data support and reference for clinical counseling.